DIPG-69. CHARACTERISTICS OF PATIENTS ≥ 10 YEARS OF AGE WITH DIFFUSE INTRINSIC PONTINE GLIOMA: A REPORT FROM THE INTERNATIONAL DIPG REGISTRY. Issue 2 (22nd June 2018) - Erker, Craig; Lane, Adam; Chaney, Brooklyn; Escorza, Nancy Yanez; Fuller, Christine; Saab, Raya; Kieran, Mark; Packer, Roger; Nazarian, Javad; Minturn, Jane; Dodgshun, Andrew; Parkin, Sarah; et al.
Abstract: INTRODUCTION: Patients ≥10 years of age with a DIPG are reported to have a higher rate of long-term survival (≥24 months). The purpose of this study was to compare clinical, radiological, pathological and molecular characteristics between patients ≥10 years old with DIPG who were long-term survivors (LTS) vs short-term survivors (STS) and assess biological differences in this age group compared to patients <10 years old. METHODS: Data were abstracted from the International DIPG Registry (IDIPGR) for patients ≥10 years old at diagnosis. Imaging was reviewed and those with typical radiographic findings of DIPG were included. The primary outcome was overall survival (OS) categorized as LTS (≥24 months) or STS (<24 months). RESULTS: Among 782 patients with abstracted data in the IDIPGR, 170 were ≥10 years of age (22%). The median age and OS [range] were 12.5 [10.0–26.8] years and 15 [2–82] months, respectively; 12.8% were LTS. Biopsy or autopsy were performed in 38% of patients; 83% of patients were H3 K27M-mutant. LTS were found to have longer symptom duration before presentation, lower WHO grade and larger tumor size compared to STS. WGS and RNA sequencing are being conducted. CONCLUSION: The rate of LTS in patients ≥10 years of age is approximately 13%. Preliminarily, clinical and imaging parameters associated with LTS in this population are similar to general DIPG cohorts. Biological data will be presented for the approximately 38% of patients with available tissue to delineate potential predictors of outcome.